The Village Landscape of Ubud, Bali: Between Cultural Heritage, Tourism, and Sustainability - Djaja Bharuna S, Anak Agung Gde; Anak Agung Ngurah Aritama (Mudra Jurnal Seni Budaya, 2025)
The unitary region of Ubud, Bali, is well-known for its unique physical and cultural landscape. Like other communities in South Bali, Ubud is a legacy of a traditional village known as desa pekraman . In terms of village environmental management, empirically inherited sociocultural norms are well-preserved. The central crossroad of the catus patha pattern is thought to serve both a religious and mystical purpose, in addition to functioning as a regional hub. The village-level implementation of the concept of the three causes of virtue ( tri hita karana ) and the religious concept of the nine land value hierarchies ( sanga mandala ) in residential units are ongoing examples of local wisdom in response to the development of tourism culture and the demands of international tourist destinations. The growth of tourism in Ubud, on the other hand, has transformed traditional patterns and integrated new cultures into the traditional ones. This transformation raises questions about the long-term viability of Ubud's traditional practices in the context new tourism economy. To what extent can Bali's culture survive as a tourist attraction? Through observation and literature studies, the landscape and environment of Ubud Village, as well as the development of environmental forms that occur due to the embodiment of the concept of local wisdom and the efforts made, will be described in anticipation of the development of cultural tourism areas. The significance of the village landscape and its application to the village environment are all explained in this essay. The article then examines Ubud Village's current condition of development.